2013
DOI: 10.1186/1471-2474-14-167
|View full text |Cite
|
Sign up to set email alerts
|

The course of radiographic loosening, pain and functional outcome around the first revision of a total hip arthroplasty

Abstract: BackgroundThe published data on pain and physical function before and after revision of total hip arthroplasty (THA) is scarce. The study reports the course and interrelationships of radiographic loosening, pain and physical function 5 year before and after a first revision THA.MethodsThe study was based on the IDES-THA database. All patients with their first THA revision for aseptic loosening and a documented index surgery on the same side and at least one pre-revision and one post-revision follow-up were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
12
1
Order By: Relevance
“…There is limited evidence on the improvement in objective function following revision hip arthroplasty but the findings are in agreement with ours[ 20 ]. Aghayev et al demonstrated the benefit of revision hip arthroplasty on the ability to walk, reporting an improvement in the percentage of their patients unable to walk for more than 30 minutes 12-months after surgery from 65% pre-operatively to 50% 12-months after surgery.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is limited evidence on the improvement in objective function following revision hip arthroplasty but the findings are in agreement with ours[ 20 ]. Aghayev et al demonstrated the benefit of revision hip arthroplasty on the ability to walk, reporting an improvement in the percentage of their patients unable to walk for more than 30 minutes 12-months after surgery from 65% pre-operatively to 50% 12-months after surgery.…”
Section: Discussionsupporting
confidence: 91%
“…The observed effectiveness of revision hip arthroplasty to improve patient-reported pain and function is consistent with the existing evidence [ 9 , 20 25 ]. The few studies measuring outcomes prior to 12 months post-operation report that changes in outcomes following revision hip arthroplasty plateau at 6-months post-operation [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 88%
“…The importance of the interpretation of these images is recognized and it is recommended that an orthopaedic surgeon or musculoskeletal radiologist or an arthroplasty practitioner with suitable training complete this (Haddad et al, ; British Orthopaedic Association, ). Although both cost and risk are associated with taking X‐ray images, they continue to form the basis of total hip arthroplasty assessment to identify degenerative changes, which cannot be predicted from symptoms alone (Aghayev et al, ; Smith et al, ). Patient‐reported outcome measures are a useful indicator of factors such as pain, function, general health or satisfaction, particularly if a change in score is measured (Murray et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that asymptomatic hips with no radiographic findings after 1 year did not require radiographic follow-up until 5 years postoperatively. 24 Aghayev et al 25 reviewed 234 revision hip arthroplasty patients to assess their presentation and symptomology before revision. This study found that pain and disability from a loose arthroplasty began approximately 4 years before revision, with 15% of patients experiencing pain at this time, and 80% experiencing pain 2 years before revision.…”
Section: Relevant Spinal Anatomymentioning
confidence: 99%
“…Additionally, walking capacity (defined as ability to walk 30 minutes) deteriorated in 65% of patients 3 years before revision. 25 Knee arthroplasty can also mimic symptoms of radiculopathy. Patients who underwent unilateral knee arthroplasty may have a decreased patellar tendon reflex.…”
Section: Relevant Spinal Anatomymentioning
confidence: 99%